Mechanical response of elevated bridge piles to adjacent deep excavation - Zhao, Ping; Qiu, Youqiang; Wang, Zhanqi; Guo, Panpan (Scientific reports, 2025)
In urban concentrated area, the disturbance caused by construction affects significantly the sustainability of adjacent existing structures. It is essential to capture the mechanical response of existing structures to adjacent deep excavation. The objective of this paper is to investigate the displacement and internal force behavior of elevated bridge piles (BP) subject to influence of deep excavation. A three-dimensional finite element model is established by taking the project of a deep excavation near elevated bridge as an example. The numerically calculated results agree well with the measured data, which verifies the established numerical model. On the basis of this model, the influence of deep excavation on the mechanical characteristics of adjacent piles is captured. The results show that the displacement, bending moment, and shear force of piles are sensitive to the excavation depth. Their magnitudes increase with the increase of excavation depth. When the excavation is completed, the maximum displacements of piles in horizontal direction and vertical direction are 2.3 mm and 10.05 mm, respectively. The maximum bending moment is 1,140.8 kN·m. The maximum and minimum shear forces are 1,206 kN and -2,282 kN, respectively. The piles are mainly under pressure. The maximum pressure is -13,116 kN. The axial force is not sensitive to the depth of excavation. The deformation and internal force of piles exhibit obvious spatial distribution characteristics, and the closer the distance to the middle of the long side of the deep excavation, the greater the value. The research results have a positive effect on the optimization of related engineering structures and the promotion of sustainable development in urban concentrated area.